STRATEGI PROMOSI WISATA PANTAI SOLOP YANG DILAKUKAN DINAS KEBUDAYAAN DAN PARIWISATA KABUPATEN INDRAGIRI HILIR - ", Muryantono; Salam, Noor Efni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
To improve the progress of a tourism object, the role of marketing is needed. Tourism marketing is defined as an effort to facilitate tourism transactions for different groups of people. The purpose of this study was to determine the direct promotion strategy and indirect promotion strategy carried out by the Department of Culture and Tourism in increasing tourist visits at Solop Beach, Indragiri Hilir Regency. The method in this research uses a qualitative approach. The research was conducted at the Department of Culture and Tourism of Indragiri Hilir Regency. The subjects in this study were 5 people, namely 1 head of the Department of Culture and Tourism of Indragiri Hilir Regency and 1 head of business development and tourism marketing in Indragiri Hilir Regency and 3 people / visitors. Collecting data using documentation, observation and interviews. Data analysis used descriptive quantitative. The results of the study explain that the direct promotion carried out by the Department of Culture and Tourism of Indragiri Hilir Regency in promoting the tourist attraction of Solop Beach is still ineffective, due to the lack of national and local activities or events that are able to introduce the natural beauty of Solop Beach. Indirect promotion by the Culture and Tourism Office of Indragiri Hilir Regency is also still not optimal in providing information about the development of Solop Beach tourism, such as the availability of updated information from both the official website and social media. The inhibiting factors in the promotion of Solop Beach tourism in Indragiri Hilir Regency include the lack of facilities and infrastructure, limited budget, remote tourist locations, quality resources and lack of awareness for traveling.Â Keywords: Promotion Strategy, Direct Promotion and Indirect Promotion